SiO2 and ZnO nanoparticles and salinity stress responses in hydroponic lettuce: selectivity, antagonism, and interactive dynamics - Lee, Chungkeun; Choi, Seunghyun; Leskovar, Daniel I. (Frontiers in Plant Science, 2025)
Salinity stress negatively affects plant growth but can also act as a eustressor, enhancing nutraceutical quality. Nanoparticles (NPs) have unique physical and chemical properties that can impact crop growth and abiotic stress responses in both beneficial and detrimental ways. This study investigated the potential of SiO2 and ZnO NPs to alleviate salinity stress or enhance nutraceutical quality by synergizing with the eustressor effects of salinity in hydroponically grown lettuce. Two-week-old lettuce seedlings (Lactuca sativa cv. Green Forest) were transplanted into a 5-L deep water culture system and grown for four weeks in a customized growth chamber set at 25 °C with 230 µmol/m2/s photosynthetic photon flux density (PPFD). The nutrient solution was maintained at an electrical conductivity (EC) of 1.5 dS/m and pH 5.8, and replenished weekly. A factorial design was employed with four salinity treatments (non-saline, 50 mM NaCl, 33.3 mM CaCl2, and 25 mM NaCl + 16.6 mM CaCl2) and three nanoparticle treatments (no-NP control, 100 ppm SiO2, and 100 ppm ZnO). Overall, NPs improved lettuce growth under non-saline conditions. Specifically, SiO2 NPs increased shoot and root biomass, root system architecture, and antioxidant enzyme activities (superoxide dismutase-SOD and glutathione reductase-GR) compared to controls, while ZnO NPs improved root biomass and architecture, and leaf chlorophyll content. Under CaCl2 stress, SiO2 NPs enhanced root growth, non-enzymatic antioxidant capacity, and antioxidant enzyme activities (catalase-CAT, ascorbate peroxidase-APX, and GR), while these improvements were not observed under NaCl and NaCl + CaCl2 stress. ZnO NPs caused greater physiological damage under CaCl2 and NaCl + CaCl2 stress compared to NaCl alone, suggesting that the interaction between ZnO NPs and CaCl2 impaired root development and water uptake, ultimately reducing PSII efficiency through oxidative damage. The synergistic effect between NPs and salinity stress was limited, observed only between SiO2 NP and CaCl2 stress in total flavonoid content. Overall, both NPs benefited hydroponic lettuce under non-saline conditions, with SiO2 NPs enhancing tolerance under CaCl2 stress, though their interaction with salinity as a eustressor was limited. These results suggest that SiO2 NPs enhance salinity tolerance in hydroponics, whereas ZnO NPs should be used with caution under saline conditions.